Effects of agricultural or gardening physical activity on cardiovascular disease and dementia-related markers via arterial stiffness, cognitive function, and cerebral white matter status: results from cross-sectional and interventional studies - Nishiwaki, Masato; Takada, Seiya; Otsuka, Shotaro; Makizako, Hyuma; Sakakima, Harutoshi; Shiomi, Naoto; Ooba, Satomi; Matsumoto, Naoyuki; Kikuchi, Kiyoshi (Frontiers in Public Health, 2025)
BackgroundAgricultural or gardening physical activity (AGPA) offers potential as a simple strategy to improve cardiovascular disease and dementia-related markers; however, the actual preventive effects remain unclear. Our objective was to investigate AGPA regarding related markers of cardiovascular disease and dementia using cross-sectional and interventional approaches.Methods and resultsIn Study 1, community-based older individuals were assessed, and 30 individuals who performed AGPA (AG group) and 30 1:1 age-, sex-, and objective activity-matched controls were cross-sectionally compared (mean age, 75 ± 6 y). Arterial stiffness (pulse wave velocity) was lower and hand-finger dexterity (pegboard test) was higher in the AG vs. control groups. The interventional results of Study 2 (secondary analysis of a randomized controlled trial) confirmed that consistent AGPA might regress white matter hyperintensities in older individuals.ConclusionOur findings suggest that consistent AGPA perse may improve cardiovascular disease and dementia-related markers in older healthy individuals via arterial stiffness, cognitive function, and cerebral white matter status. This information could have major implications for integrated strategies for lifelong health.Secondary analysis of clinical trials (study 2)Study for Decreasing Depressive Symptoms and Increasing Memory Performance in the older adults (Trial registration number UMIN000018547, Date of registration 2015/08/07), URL: https://center6.umin.ac.jp/cgi-open-bin/ctr/ctr_view.cgi?recptno=R000021462.